Microelement Integration Drives Smart Manufacturing: A Mixed Method Study - Chenguang Li; Jingtong Gong; Tao Fu; Zhiguo Liang (Systems)
Smart manufacturing is an important initiative to promote the transformation and upgrading of industries and the high-quality development of the economy. However, the current situation of digitalized smart transformation in manufacturing enterprises is not optimistic, which is primarily attributed to the ambiguity surrounding the pathways. This study is based on the technology-organization-environment-individual (TOE-I) analytical framework; it selects 20 case studies of advanced manufacturing enterprises; and employs case studies and necessary condition fuzzy set qualitative comparative research methods (NCA and fsQCA) to investigate the pathways through which technology, organization, the environment, and individual microelements synergistically drive smart manufacturing from a configurational perspective. The study reveals that digital technology breakthroughs, digital infrastructure, digital talent, digital sharing, organizational resilience, organizational culture, and the entrepreneurial spirit are the core influencing factors in advancing smart manufacturing for manufacturing enterprises, and four implementation paths driven by smart manufacturing are analyzed. Among them, digital technology breakthroughs and digital infrastructure have a potential substitutive relationship in the “technology + talent” empowerment organizational model. Organizational resilience, organizational culture, and the entrepreneurial spirit are important safeguards for successful advancements in smart manufacturing. In contrast, digital infrastructure plays a more indirect, supporting role. Accordingly, this paper provides theoretical reference and practical guidance.